2017
DOI: 10.1016/j.bbrc.2017.08.112
|View full text |Cite
|
Sign up to set email alerts
|

Cytoskeletal remodeling via Rho GTPases during oxidative and thermal stress in Caenorhabditis elegans

Abstract: Biological systems are highly sensitive to changes in their environment. Indeed, the molecular basis of the environmental stress response suggests that the specialized stress responses share more commonalities than previously believed. Here, we used the nematode C. elegans to gain insight into the role of Rho signaling during two common environmental challenges, oxidative and thermal stress. In response to heat shock (HS), wild type (N2) worms demonstrated reduced viability which was rescued by genetic suppres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Some studies suggested that the phosphorylation of RhoGDIα is a vital mechanism to regulate the spatial interaction of RhoGDIα with Rho GTPases (Hodgson et al, 2016;Shcherbakova et al, 2018). Rho GTPases signaling is influenced by the extracellular environment, and shear stress can mediate RhoGDIα expression and Rac1 activity (Patel et al, 2017;Qi et al, 2008). The role of specific phoshphorylations of RhoGDIα in the regulation of its activity under shear stress is investigated in the present study.…”
Section: Discussionmentioning
confidence: 88%
“…Some studies suggested that the phosphorylation of RhoGDIα is a vital mechanism to regulate the spatial interaction of RhoGDIα with Rho GTPases (Hodgson et al, 2016;Shcherbakova et al, 2018). Rho GTPases signaling is influenced by the extracellular environment, and shear stress can mediate RhoGDIα expression and Rac1 activity (Patel et al, 2017;Qi et al, 2008). The role of specific phoshphorylations of RhoGDIα in the regulation of its activity under shear stress is investigated in the present study.…”
Section: Discussionmentioning
confidence: 88%
“…Upon activation by oxidative stress, Nrf2 translocates into the nucleus and binds to AREs, promoting the transcription of a wide variety of antioxidant genes [ 39 ]. Another potential mechanism is the Rho/Rho-kinase (ROCK) signaling pathway, which can modulate actin cytoskeleton organization in response to oxidative stress [ 40 , 41 ]. It was reported that activating Rho signaling partially restored the cell stiffness destroyed by oxidative stress and decreased the intracellular ROS level [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…[33] These proteins could stabilize proteins that are being formed and remodel proteins that have suffered damage and are modified. [34] The sun naturally emits ultraviolet radiation, but a large part does not reach the atmosphere due to the ozone layer present around the Earth, this radiation can cause immuno-logical and skin damage, in the case of chronic exposure it can lead to irreversible damage and aging. [35] The concentration of 100 and 250 μg of GAE/mL of jaboticaba extract showed the ability to protect the nematodes against acute UV exposure on days 3, 5 and 7, while the concentration of 50 μg of GAE/mL showed these effects on days 5 and 7 (Figure 3D and E).…”
Section: Extract Of Jaboticaba Is Able To Promote Resistance To Oxida...mentioning
confidence: 99%